Free Radical Polymerization of Methyl Methacrylate Using Anthracene Iodine Charge Transfer Complex as Novel Chain Transfer Agent - Varshney, Anuradha; Prajapati, Kiran; Jain, Nalini (Asian Journal of Chemistry, 2011)
Free radical polymerization of methyl methacrylate initiated by a,a'-azobisisobutyronitrile and anthracene iodine charge transfer complex as novel chain transfer agent was studied in DMSO at 60 ± 0.1 ºC for 2 h under oxygen free condition. The system followed ideal kinetics. The overall activation energy is 43.5 kJ/mol. The average molecular weight is in between 32608- 62662. The FTIR spectra shows band at 3020 and 1725 cm-1 due to phenyl protons of anthracene charge transfer complex and ester stretching of methyl methacrylate, respectively. The 1H NMR spectra confirms the methoxy protons at 3.7 d ppm. Thermogravimetric analysis shows the stability of polymer upto 230 ºC.